Learning Factors in Informal Digital Spaces: A Study of English Learning Through TikTok Content by @englishramah - Mahfudz Azwar; Dinnurrizki Fajrullah; Nuzula Ahmad; Zuhdi Ibadulloh; Fahriany (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Social media has changed the way people learn languages outside of a classroom. TikTok specifically, as an interface of demand for English learning, with its amusing and accessible contents in short forms. However, research on learning factors that affect English acquisition in informal digital spaces is scarce particularly concerning educational content creators such as @englishramah. This research employed a qualitative descriptive design involving online semi-structured interviews with ten TikTok users and observations of selected videos. The data were analyzed thematically to identify patterns related to learner motivation, interaction, and content accessibility. This research argues to investigate these learning factors on English language development in the use of TikTok including learner motivation, interaction and content accessibility. With a view to explore the concepts and categories, data were gathered from ten TikTok users as key informants who actively consume @englishramah’s content through online interviews for data collection and select videos for observations of their content. The findings reveal that delivery attractiveness is the most influential factor in sustaining learners’ engagement, followed by clarity of explanations supported by real-life examples and an informal tutor delivery style. These factors contribute to increased motivation, comprehension, confidence, and perceived improvement in English ability.